The Aging Muscle in Experimental Bed Rest: A Systematic Review and Meta-Analysis - Di Girolamo, Filippo Giorgio; Fiotti, Nicola; Milanović, Zoran; Situlin, Roberta; Mearelli, Filippo; Vinci, Pierandrea; Šimunič, Boštjan; Pišot, Rado; Narici, Marco; Biolo, Gianni (Frontiers in Nutrition, 2021)
Maintaining skeletal muscle mass and function in ageing is crucial for preserving quality of life and health. Physical inactivity, especially in elderly adults, is a key factor in the onset of muscle loss and function decline. Experimental bed rest (BR) is a suitable model to explore muscle loss in ageing compounded by inactivity. The present systematic review and meta-analysis clusters the available data on muscle mass, strength, power and functional capacity changes from a total of 22 bed rest papers on 118 healthy elderly volunteers undergoing 5-, 7-, 10- or 14-days BR and provides a brief sketch on the possible mechanisms involved. In the very early phase of BR, important changes occur in skeletal muscle, with significant loss of performance associated with a smaller reduction in total body and muscle mass. Further prolonging the BR period induces a progressively greater decline compared to a 5 days protocol, with protein breakdown accounting for the initial muscle loss (1-7 days) and reduced protein synthesis accounting for muscle loss thereafter. Muscle lower limb mass shows a consistent progressive reduction throughout the BR studies, reaching 8% after 14 days. Younger controls are less prone to such early loss and are also more prompt in muscle recovery after rehabilitation. Muscle decline in ageing and inactivity is associated with resistance to post-prandial anabolic stimulation of protein synthesis. Anabolic resistance induced by experimental bed rest is much greater in the elderly as compared to a younger population. Mechanisms underlying the greater loss of muscle mass and function and the enhanced anabolic resistance in ageing following inactivity need to be thoroughly investigated